2015
DOI: 10.3892/ol.2015.2959
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for gastric cancer: Progression in early diagnosis and prognosis (Review)

Abstract: Gastric cancer is one of leading causes of cancer-related mortality worldwide and is a notable disease due to its heterogeneity. Recently, numerous studies have investigated the molecular basis of gastric cancer, involving the alteration of pathogenesis, and invasion and metastasis. With the development of modern technologies, various novel biomarkers had been identified that appear to possess diagnostic and prognostic value; therefore, the present review describes our current knowledge of biomarkers for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 102 publications
2
61
0
Order By: Relevance
“…Because of a lack of understanding regarding the pathogenesis of GC and the lack of a specific targeted gene therapy, chemotherapy, and surgical techniques do not satisfactorily enhance the survival rate of patients with GC . Some studies have indicated that genetic alteration may play a crucial role in the development of GC and carcinogenesis . Several genetic alterations which can be used as prognostic biomarkers include oncoproteins such as protein kinase CK2, VAV3, and SOX4, as found in our laboratory, and tumor suppressors such as miR‐429 and miR‐1225‐5p, as found in other laboratories .…”
Section: Introductionmentioning
confidence: 57%
“…Because of a lack of understanding regarding the pathogenesis of GC and the lack of a specific targeted gene therapy, chemotherapy, and surgical techniques do not satisfactorily enhance the survival rate of patients with GC . Some studies have indicated that genetic alteration may play a crucial role in the development of GC and carcinogenesis . Several genetic alterations which can be used as prognostic biomarkers include oncoproteins such as protein kinase CK2, VAV3, and SOX4, as found in our laboratory, and tumor suppressors such as miR‐429 and miR‐1225‐5p, as found in other laboratories .…”
Section: Introductionmentioning
confidence: 57%
“…Studies show that dysfunction of intrinsic miRNA regulatory mechanisms results in abnormal expression of various oncogenes and tumor suppressor genes in a variety of tumor types (18); therefore, miRNAs may act as both oncogenes and tumor suppressor genes. miRNAs have been implicated in the biology of gastric cancer (19,20): miRNA array analysis has shown that expression of miR-21, miR-191, miR-223, miR-24, miR-107, miR-92 and miR-221 is elevated in gastric cancer (21), while that of miR-128b, miR-129 and miR-148 is decreased (22). Gastric cancer is a disease involving the complex activation and inactivation of multiple genes; miRNAs may therefore assume the role of both oncogene and tumor suppressor in the onset and development of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is the most common epigenetic modification, and is involved in various biological processes, including tumorigenesis, when aberrant DNA methylation occurring in promoter CpG islands can lead to gain of function in oncogenes and loss of function in tumor suppressor genes (1)(2)(3)(4). The mechanism by which DNA hypomethylation contributes to tumorigenesis has been proposed to involve chromosomal instability (5,6), derepression of imprinted genes (7), and retrotransposon activation (8,9).…”
Section: Introductionmentioning
confidence: 99%